Modification of Drain Hayward Strainer Pipe Header Pipes to Improve Efforts of Cooling Water Pump Train EF Badak LNG Bontang - Murni, Murni; Ferdiyanto, Riky; Darmanto, Seno; Ariwibowo, Didik (Journal of Vocational Studies on Applied Research, 2019)
In Badak LNG the role of the cooling water pump is very important, and becomes the main support for transferring sea water where the water is used in the cooling process of industrial machinery or as emergency safety for firefighters. Water pump cooling has a hayward strainer that serves to filter water with a smaller filter so that the cooling water that is sent is completely free of dirty water. The purpose of this final project is to find out the main causes of the performance degradation of the EF cooling water pump due to the barrier to the hayward strainer which results in lower pressure on the cooling water. The methodology applied was based on field observations and conducted a solidwork simulation test. Field observations show that when more than one hayward strainer is in backwash, the effectiveness of backwash release decreases because the main disposal of the hayward strainer becomes one. The solidwork simulation found that the pressure on the Hayward train E strainer was high enough to create back pressure and limit the flow of the Hayward strainer outlet. By performing actual simulations by only running only one exhaust system at Hayward train E trainer has improved performance on the hayward strainer system. The performance analysis of the cooling water pump was carried out to determine the cause of the pump pressure drop on the hayward strainer and it was found that the main cause of performance was due to back pressure disposal, the pressure was increasing at each outlet of the Hayward strainer which had more distance to the outlet drain. Taking into account the problem of back pressure, separating the train E and F cooling water pump lines is a good choice. After simulating solid work, the separation of the E train line and the F colling water train shows an increase in the performance of the cooling water pump system because the Hayward strainer runs well so that the pump pressure is maintained for the industrial engine cooling needs.